Digital Storytelling for Teaching EFL Process Reading and Writing (Global Journal of Human-Social Science, 2022)
A 6-month action research carried out with two classes of 6 th Graders in a state primary school in Greece investigated whether the telling of stories in electronic form Reinders 2011 p 2 could enhance young EFL learners reading and writing skills in terms of the Waystage A2 criteria of language competence specified by the State Certificate of Language Proficiency The control group was taught through the official textbook whereas the experimental group engaged in interactive reading and computer-assisted collaborative process writing with a view to producing the script for their digital narrations The research findings verified the researchers initial assumptions concerning the favorable impact of digital storytelling on the reading and writing skills of the experimental group Their significance lies in that they offer EFL teachers more options to enhance their learners reading and writing skills
Keywords: digital storytelling; interactive reading; process writing; collaborative writing; primary school learners